2010
DOI: 10.2106/jbjs.i.01170
|View full text |Cite
|
Sign up to set email alerts
|

Driving with an Arm Immobilized in a Splint: A Randomized Higher-Order Crossover Trial

Abstract: Driving performance as measured with a standardized track and scoring system was significantly degraded with splint immobilization of the left arm. Further studies are required to determine the effect of arm immobilization on normal driving conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 10 publications
0
48
0
6
Order By: Relevance
“…Tests of braking function are not applicable with upper extremity surgeries. Healthy patients driving on courses indicated that it is unsafe for patients with most forms of upper extremity immobilization to drive [6,7,20,21]. A driving simulator that includes avoiding obstacles could be a better method of evaluating driving ability than an isolated evaluation of braking function, as there is more to driving and avoiding accidents than accounting for the time it takes to press the brake pedal.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Tests of braking function are not applicable with upper extremity surgeries. Healthy patients driving on courses indicated that it is unsafe for patients with most forms of upper extremity immobilization to drive [6,7,20,21]. A driving simulator that includes avoiding obstacles could be a better method of evaluating driving ability than an isolated evaluation of braking function, as there is more to driving and avoiding accidents than accounting for the time it takes to press the brake pedal.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these articles discussed procedures that were not on our original list, one was not indexed in either database, one did not have driving as a primary focus, and the remaining six articles discussed driving with limb immobilization. Thirty-four articles had data relevant to our study Question 1 [1, 4, 5, 9, 10, 12, 13, 15, 19, 22, 23, 26-30, 34, 36, 37, 39, 41, 42, 45-50, 53, 55, 57, 60, 63, 64], eight had data relevant to Question 2 [2,6,7,17,20,21,43,46], and seven had data relevant to Question 3 [3,31,32,35,54,58,59] (Table 1). The range of MINORS scores for comparative studies was 17 to 24, and the range for noncomparative studies was 11 to 15.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,103 The risks of immobilization are difficult to quantify, but can include difficulty performing fine hand tasks, diminished driving performance, decreased ability to perform work-related tasks, and pain or pruritis discomfort requiring splint removal. 104,105 The risk of splint-related complications requiring further management was estimated at 6.7% in one recent meta-analysis. 105 In nondisplaced fractures, multiple systematic reviews demonstrate no advantage to operative management or splints in reducing nonunion rates or patient discomfort.…”
Section: Test-treatment Thresholdmentioning
confidence: 99%